Determination of Interrogating Frequencies to Maximize Electromagnetic Backscatter from Objects with Material Coatings (Communications in Computational Physics, 2018)
The electromagnetic backscattering of a crosscut of a cruise missile coatedby a thin homogeneous layer made of radar absorbent material is modeled using afinite element method. Based on the radar cross section and a reflection coefficient,optimization problems are formulated for evaders and interrogators leading to optimalmaterial parameters for the coating and optimal monostatic radar operating frequencies,respectively. Optimal coating materials are constructed for several radar frequencies.Tuning only dielectric permittivity gives a narrow frequency range of high absorptionwhile also tuning magnetic permeability widens it significantly. However the coatinglayers considered do not provide substantial reduction of backscattering in the entirefrequency range from 0.2 to 1.6 GHz. Computational experiments also demonstratethat the reflection coefficient based on a simple planar geometry can predict well thestrength of radar cross section in the sector of interest with a substantially reducedcomputational burden.